Complications following liver resection for colorectal metastases do not impact on longterm outcome. Issue 2 (February 2015) - Pang, Tony C.; Spiro, Calista; Ramacciotti, Tim; Choi, Julian; Drummond, Martin; Sweeney, Edmund; Samra, Jaswinder S.; Hugh, Thomas J.
Abstract: Background: It has been suggested that adverse postoperative outcomes may have a negative impact on longterm survival in patients with colorectal liver metastases. Objectives: This study was conducted to evaluate the prognostic impact of postoperative complications in patients submitted to a potentially curative resection of colorectal liver metastases. Methods: A retrospective analysis of outcomes in 199 patients submitted to hepatic resection with curative intent for metastatic colorectal cancer during 1999–2008 was conducted. Results: The overall complication rate was 38% ( n = 75). Of all complications, 79% were minor (Grades I or II). There were five deaths (3%). The median length of follow‐up was 39 months. Rates of 5‐year overall and disease‐free survival were 44% and 27%, respectively. Univariate analysis demonstrated that an elevated preoperative level of carcinoembryonic antigen (CEA), intraoperative blood loss of >300 ml, multiple metastases, large (≥35 mm) metastases and resection margins of <1 mm were associated with poor overall and disease‐free survival. In addition, male sex and synchronous metastases were associated with poor disease‐free survival. Postoperative complications did not have an impact on either survival measure. The multivariate model did not include complications as a predictive factor. Conclusions: Postoperative complications were not found to influence overall or disease‐free survival in the present series. The number and size of liver metastases were confirmed as significant prognostic factors.